Franklin tragic hero of polar navigation - Lambert, Andrew D. 1956- (Faber and Faber, 2009)
The gripping story of the worst ever catastrophe in British exploration, and the captain at the heart of it, Sir John Franklin, who was also Governor of Tasmania.